Faktor Risiko Kejadian Pre Eklampsia Pada Ibu Hamil - Harmin, Yeyen Anugrah; Palupessy, Nugraha; Muthalib, Abdul (Innovative: Journal Of Social Science Research, 2024)
Preeclampsia is a serious pregnancy complication that requires an in-depth understanding of risk factors for effective prevention and treatment. This study used a literature review method to evaluate various risk factors for preeclampsia, including demographics, pre-pregnancy health conditions, as well as genetics and environment. The results showed that older maternal age, lower socio-economic status, and pre-pregnancy conditions such as hypertension and diabetes significantly increased the risk of preeclampsia. In addition, genetic and environmental factors also contribute to this risk. The conclusions of this study emphasize the need for a multifaceted approach in preeclampsia prevention and management strategies, which includes health monitoring, lifestyle modification, and attention to environmental factors.